THE EFFECT OF PROFITABILITY, SALES GROWTH AND COMPANY AGE ON MINING COMPANIES’ TAX AVOIDANCE - Tantono, Jackie; Irena, Angela; Putri, Melati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Tax avoidance is usually influenced by various things including profitability, sales growth, and company age. Large profits will result in large tax costs, so management prefers to minimize tax costs by avoiding taxes. The population used in this research is all mining sector companies listed on the Indonesian Stock Exchange which is as much as 63 companies. The sampling technique used is purposive sampling, resulting in 10 companies and a total of 40 samples. The results of the study indicate that Profitability partially has a significant impact on mining sector companies listed on the Indonesia Stock Exchange (IDX). Sales Growth partially has a significant impact on mining sector companies listed on the Indonesia Stock Exchange (IDX). Company Age partially has no significant impact on mining sector companies listed on the Indonesia Stock Exchange (IDX). Profitability, Sales Growth, and Company Age simultaneously have a significant impact on Tax Avoidance in the mining sector companies listed on the Indonesia Stock Exchange (IDX).